Substrate stoichiometry and microbial metabolic preference drive the divergent accumulation of plant and microbial necromass carbon in cropland soils: evidence from a short-term experiment - Wu, Hongliang; Wang, Luming; Liu, Xiuping; Wang, Wenyan; Lu, Changai; Dong, Wenxu (Frontiers in Microbiology, 2025)
Substrate input and subsequent ex vivo modification and in vivo turnover mediated by microbial systems determine the formation of soil organic carbon (C). However, the effects and mechanisms by which substrate stoichiometry (SS) adapts to microbial metabolic preferences and influences the dynamics of plant and microbial necromass C (PNC, MNC) remain unclear. Therefore, the variations and controlling factors of PNC and MNC in top- (0–20 cm) and subsoil (20–40 cm) across different SS conditions were investigated during the whole maize season. Mainly, the SS of exogenous C, nitrogen (N), phosphorus (P), and sulfur (S) meet the metabolic requirements of fungi (NPS1) and bacteria (NPS3). Results showed that compared to NPS1, NPS3 increased MNC by 5.3% in topsoil and 13.9% in subsoil, while reducing PNC by 7.0% and 16.3%, respectively. These suggested that SS matching bacterial needs could accelerate the digestion of PNC and enhanced the accumulation of MNC, especially in subsoil. Under NPS1, dominant microbial taxa (e.g., Planctomycetota), phosphatase, and nutrient availability were key determinants of necromass C (NC) changes, with MNC and PNC being predominantly influenced by available N and P, respectively. Firmicutes was particularly influential in the subsoil. Under NPS3, a more diverse bacteria, including Proteobacteria, was mobilized, with β-glucosidase and available N being central to NC variations. Changes in PNC were also primarily regulated by fungi, specifically Mortierellomycota. Our findings of the short-term experiment suggest that SS influences the digestion or accumulation of PNC and MNC by regulating nutrient availability, C and P cycling enzymes, and functional flora, and meanwhile, emphasize that SS matching bacterial requirements enhances MNC accumulation.